(untitled) (Universal xalqaro ilmiy jurnal, 2026)
In this work, LaFeO₃ perovskite nanomaterial was synthesized via an environmentally friendly green synthesis route using the alcoholic extract of Allochrusa gypsophiloides. The structural, functional, and elemental characteristics of the synthesized sample were comprehensively investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and energy-dispersive X-ray spectroscopy (EDX), respectively. The XRD results confirmed the formation of a single-phase orthorhombic perovskite structure without any detectable impurities. FTIR spectra revealed characteristic absorption bands corresponding to Fe–O and La–O bonds. Elemental analysis indicated that the mass percentages of La₂O₃ and Fe₂O₃ were 47.8% and 52.2%, respectively, demonstrating good stoichiometric agreement. The obtained results confirm the effectiveness, simplicity, and environmental sustainability of the green synthesis approach for producing high-purity LaFeO₃ nanomaterials with promising catalytic and photocatalytic applications